The future technology development in the Philippine Printing Industry a technology foresight study using environmental scan and relevance tree analysis - Gloria, Jesli C.; Imbang, Glenn (Quezon City University of the Philippines Diliman, 2014)
The printing industry is one significant workforce of the society and is considered vital in defining a remarkable growth to the Philippine economy. This compelling truth is supported by real-world cases and information, based on studies and interviews of major players in the country. To further establish its reliability, a comprehensive study is prepared to provide a unique overview on the development and technological advances on how the printing industry can greatly influence its success in a long term scenario. The study uses global environmental techniques such as environmental scanning and relevance tree analysis to interpret an industry level approach which comprises industries, markets, companies, clients and competitors. The results of the two methods collectively reveals major trends and other environmental phenomenon and how these technologies create a tremendous impact in the evolution of the printing industry. There are sets of strategies that were generated to address firm level, industry level and government level future actions that could be considered in scenario building and technology roadmap exercises.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Technological forecasting -- Philippines; Printing industry -- Philippines; Technology development; Technology foresight; Environmental scanning; Relevance tree analysis